1995
DOI: 10.1159/000282754
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Parameter Immunoflow Cytometry – A New Technique in the Noninvasive Diagnosis of Bladder Cancer

Abstract: The introduction of monoclonal antibodies into the diagnosis of transitional cell carcinoma (TCC) has been a further step toward the use of biological parameters to support conventional cytological diagnosis of this tumor entity. Several investigators have demonstrated the high sensitivity and good specificity of immunocytology. Nevertheless this technique is hampered by the inconvenient and time-consuming microscopic analysis. The purpose of this study was to combine the advantages of immunocytology with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The examination of specimens from patients with endoscopically and pathologically proven TCC, irrespective of concomitant urinary tract infection, confirms the high sensitivity (95%) of immuno-FCM observed earlier in a smaller study population [4]. The detection of all 10 cases with G1 tumors is remarkable and confirms the results of earlier immunocytological observations [8, 9, 10, 11].…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The examination of specimens from patients with endoscopically and pathologically proven TCC, irrespective of concomitant urinary tract infection, confirms the high sensitivity (95%) of immuno-FCM observed earlier in a smaller study population [4]. The detection of all 10 cases with G1 tumors is remarkable and confirms the results of earlier immunocytological observations [8, 9, 10, 11].…”
Section: Discussionsupporting
confidence: 86%
“…Evaluation of Lewis X antigen reactivity in bladder irrigation specimens from bladder cancer patients by Sheinfeld and associates [10]revealed that in 90% of the positive specimens the antigen was expressed in 25% or more of the epithelial cells. Our experience with immunocytology and earlier investigations showed that the 25% cutoff value of ABC 3-positive cells among all urothelial cells yielded an optimal discrimination between healthy donors and patients with transitional cell carcinoma [3, 4, 8, 9]. …”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations